Determining Forage Quality Values of Salvia multicaulis VAHL. Species Collected From Different Locations of the Southeastern Anatolia Region of Turkey - Mehmet Başbağ; Mehmet Salih Sayar; Erdal Çaçan (Turkish Journal of Agriculture: Food Science and Technology)
The study was conducted to determine forage quality criteria of Salvia multicaulis VAHL. species collected from different locations of Southeastern Anatolia Region of Turkey in 2018. Results of statistical analysis of the study data revealed that there were significant differences among the locations for all of the investigated traits. Additionally, among the locations the investigated traits were changed as following; dry matter content (DM) 88.66-91.58%, crude protein content (CP) 16.47-25.37%, insoluble protein content in acid detergent (ADP) 0.8%-1.10%, acid detergent fiber content (ADF) 22.08-29.54%, neutral detergent fiber content (NDF) 29.71-%43.85%, calcium (Ca) content 1.22-1.82%, phosphor (P) content 0.23-0,40%, Ca:P ratio 3.05-6.87, potassium (K) content 1.20-2.58%, magnesium (Mg) content 0.28-0.46% and K/(Ca+Mg) ratio 0.55-1.44. Results of the study revealed that dry forage of Salvia multicaulis species is both rich in terms of crude protein content and having a high digestibility level and its macro minerals content and K/(Ca+Mg) ratio to be sufficient for animal feeding. However, due to its too high level Ca:P ratio than critical top level (2:1), it is important to be careful against the risk of poisoning of animals when the forages of this species are used in animal feeding. Hence, additional research is required to determine the harmful effect of the species on the livestock health.